Technological development and impact on economic and environmental sustainability - Bayar, Yilmaz, 1977-; Sasmaz, Mahmut, 1986-; Öztürk, Ömer, 1981- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2022)
"The book investigates the technological development and its impact on economic and environmental sustainability in the world from an interdisciplinary perspective"--